Comparison of oxycodone and fentanyl for postoperative patient-controlled analgesia after laparoscopic gynecological surgery - Park, Joong-Ho (Korean J Anesthesiol, 2015)
BACKGROUND: Opioids are widely used in boluses and patient-controlled analgesia (PCA) for postoperative pain control. In this study, we compared the effects of oxycodone and fentanyl on postoperative pain in patients with intravenous patient-controlled analgesia (IV-PCA) after laparoscopic gynecological surgery. METHODS: Seventy-four patients undergoing elective total laparoscopic hysterectomy or laparoscopic myomectomy were randomly assigned to the administration of either fentanyl or oxycodone using IV-PCA (potency ratio 1 : 60). The cumulative dose administered in the patient-controlled mode during the initial 48 hours after the operation was measured. Patients were also assessed for postoperative pain severity, adverse effects, and patient satisfaction. RESULTS: No significant differences were observed in patient satisfaction with the analgesia during the postoperative period. Patients in the oxycodone group experienced significantly more dizziness compared to the fentanyl group. Patients in the oxycodone group showed significantly lower consumption of opioid in the patient-controlled mode (10.1 ± 8.5 ml vs. 16.6 ± 12.0 ml, P = 0.013). CONCLUSIONS: Our data suggest that oxycodone and fentanyl demonstrated similar effects, and therefore oxycodone may be a good alternative to fentanyl in postoperative pain management. Further studies in various clinical settings will be needed to determine the adequate potency ratio.